Consent and the Problem of Framing Effects - Hanna, Jason (Ethical theory and moral practice, 2011)
Our decision-making is often subject to framing effects: alternative but equally informative descriptions of the same options elicit different choices. When a decision-maker is vulnerable to framing, she may consent under one description of the act, which suggests that she has waived her right, yet be disposed to dissent under an equally informative description of the act, which suggests that she has not waived her right. I argue that in such a case the decision-maker’s consent is simply irrelevant to the permissibility of proceeding. I then consider two alternative views. According to the first, people susceptible to framing are able to give valid consent so long as they are sufficiently informed. This suggestion, I argue, maintains an overly narrow focus on mere quantity of information to the exclusion of other choice-affecting factors. A second response, which appeals to hypothetical consent, is likewise of little use in resolving the moral problem posed by framing effects. I conclude that if susceptibility to framing undermines the validity of consent, we may have good reason to reconsider whether consent has the rights-waiving function commonly attributed to it.